The standard theory of administrative unlawfulness - Adams, T (Cambridge University Press, 2017)
According to the standard theory of administrative unlawfulness an act that is public law unlawful is, for that reason, invalid and of no effect in law. In this article I suggest that the theory ought to be rejected. I begin by outlining the standard theory as well as noting its endorsement by the Supreme Court in the case of Ahmed (no. 2). Having in the main part of the paper criticised the theory, I move to lay out an alternative: that unlawfulness signals not the invalidity of an administrative act but a duty on the part of the court to invalidate it. Noting that the alternative rests upon what appears to be a paradox – that unlawful administrative action may nonetheless have legal effect – I try to show why it is more apparent than real. Finally, I return to the decision in Ahmed (no. 2).